2002
DOI: 10.1007/s11745-002-0880-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n−3 PUFA alter colonocyte mitochondrial membrane composition and function

Abstract: There is experimental evidence that dietary fish oil, which contains the n-3 fatty acid family, i.e., EPA and DHA, protects against colon tumor development, in part by increasing apoptosis. Since mitochondria can act as central executioners of apoptosis, we hypothesized that EPA and DHA incorporation into colonocyte mitochondrial membranes, owing to their high degree of unsaturation, would enhance susceptibility to damage by reactive oxygen species (ROS) generated via oxidative phosphorylation. This, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 36 publications
5
54
0
1
Order By: Relevance
“…Other mechanisms have been proposed to explain the cell growth inhibitory effect of EPA. Studies have indicated, for example, that dietary EPA and DHA can induce compositional changes in colonic mitochondrial membrane phospholipids that may, in turn, facilitate their inhibitory effect on cell proliferation as well as the induction of apoptosis in tumor cells (2,33). To our knowledge, this is the first study to demonstrate that PGE 3 produces antiproliferative effects on human nonsmall cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…Other mechanisms have been proposed to explain the cell growth inhibitory effect of EPA. Studies have indicated, for example, that dietary EPA and DHA can induce compositional changes in colonic mitochondrial membrane phospholipids that may, in turn, facilitate their inhibitory effect on cell proliferation as well as the induction of apoptosis in tumor cells (2,33). To our knowledge, this is the first study to demonstrate that PGE 3 produces antiproliferative effects on human nonsmall cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…The researchers found that the effects on colon cell proliferation depend on the type of fat (corn oil, fish oil or beef tallow) and fibre (pectin, cellulose) as well as of their combinations and reported several mechanisms of the effects observed. They showed that an important aspect of common DHA and butyrate effects is potentiation of the intrinsic mitochondrial apoptotic pathway 142 . Mitochondria also play a very important role in the maintenance of Ca2+ homeostasis, which is synergistically imbalanced by DHA and butyrate treatment, causing mitochondrial Ca2+ accumulation and peroxidation which triggers apoptosis in a p53-independent manner 143 .…”
Section: Interaction Of Dha With Butyratementioning
confidence: 99%
“…58 Also, feeding of fish oil or purified n-3 fatty acid ethyl esters selectively increased EPA and DHA levels in the mitochondrial phosplolipids of colonocytes at the expense of n-6 fatty acids. 60 It has been shown that inhibition of colon carcinogenesis by DHA is mediated through the activation of retinoid X receptors (RXRs), a obligatory component of a large number of nuclear receptors, 61 suggesting n-3 PUFAs mediate growth inhibitory effects in the colon through the RXR subunit of nuclear receptor heterodimers. Members of the nuclear receptor superfamily are transcription factors that selectively regulate cell differentiation and proliferation.…”
Section: Possible Mode Of Action Of Types Of Dietary Fat In Colon Carmentioning
confidence: 99%